A comparative study on different glycerol concentration of banana (Musa acuminata) and orange (Citrus sinensis) peels in the production of pectin-based biopolymer films - Ranido, Jersy Pauline A. (Animo Repository, 2022)
The search in developing sustainable and environmentally-friendly material of biopolymer film for food packaging from natural biopolymers such as pectin. The research evaluates the physico-chemical, mechanical, thermal properties and biodegradability of pectin-based film extracted from banana and orange peel in different glycerol concentrations (30, 40 and 50%). Pectin was obtained from solvent extraction using HCl and casting method was used in the synthesis of the biopolymer film. The thickness of both pectin films was directly proportional to the glycerol concentration. However, the moisture content was highest for 40 and 30% glycerol concentration from banana and orange pectin films. With glycerol concentration increasing, the attraction between water molecules increases due to the presence of hydroxyl groups. More unbinded water molecules is an indication of a high moisture content, resulting in a decrease of quality in the biopolymer film. Thermal analysis revealed that glycerol concentration had no significant effect on the thermal stability of orange peel pectin-based film (OPPF). However, in banana peel pectin-based film (BPPF), 40% glycerol as plasticizer showed the highest thermal stability with Tg and Tm of 191.78 and 217.57, respectively. The OPPF exhibited an increase in tensile strength (TS) and elastic modulus (EM) of 18 - 48.50 KPa and 71.11 - 62.78% with higher glycerol concentration while BPPF was too fragile to test, indicating the OPPF had better mechanical properties than BPPF. In the case of mechanical properties, SEM images supported the results due to the surface irregularities, crack, porous and agglomerate formation found in BPPF. Total biodegradation of both the OPPF and BPPF were observed in less than 60 minutes in the soil burial assay. Overall, these results suggest that films mixed with glycerol as plasticizer have a great potential to be fabricated as environmentally-friendly and biodegradable plastics.